GENE-17. TUMOR-DERIVED CELL-FREE DNA MAY BE FREQUENTLY DETECTED BY CLINICAL TARGETED SEQUENCING OF CEREBROSPINAL FLUID IN CHILDREN WITH BRAIN TUMORS. (23rd April 2019) - Karvonen, Kristine; Lockwood, Christina; Cole, Bonnie; Stasi, Shannon; Stevens, Jeff; Hauptman, Jason; Lee, Amy; Leary, Sarah
Abstract: INTRODUCTION: Targeted sequencing of somatic DNA obtained from pediatric brain tumor tissue is of clinical utility in forming an integrated molecular and histologic diagnosis as well as evaluating therapeutic targets. The evaluation of cell-free DNA (cfDNA) from blood or cerebrospinal fluid (CSF) has not yet been clinically validated in pediatric brain tumors. METHODS: Using a clinically validated targeted 262 next-generation gene sequencing platform, we evaluated cfDNA in 15 subjects with CSF and plasma samples paired with pediatric brain tumor tissue including medulloblastoma (n=7), atypical teratoid-rhabdoid tumor (n=2), diffuse midline glioma (n=4), pilocytic astrocytoma and pleomorphic xanthoastrocytoma (n=1 each). Informed consent was obtained from all subjects and this study was approved by the institutional review board. CSF was obtained at the time of surgery or from ventriculostomy in 3 cases each, and from diagnostic lumbar puncture in the remainder. RESULTS: cfDNA from CSF was successfully isolated from 8/15 (53%) subjects, and was sufficient for sequencing in 6/8 samples. Somatic mutations and copy-number changes found in cfDNA from CSF corresponded to changes found by tumor sequencing in all cases. Tumor-derived cfDNA was detected in as little as 200 microliters of CSF, and in the absence of cytological evidence of tumor. Tumor-derived cfDNA was not detected in plasma samples. CONCLUSION: The evaluation of cfDNA from CSF shows promise for clinical applications in pediatric brain tumor diagnosis and disease monitoring. A longitudinal prospective study of cfDNA detection in CSF for disease monitoring is planned.